Transcending telemedicine: exploring telemedicine adoption perspectives of physicians - Naga, January Febro; Sison, Raymund C. (International Journal of Public Health Science (IJPHS), 2025)
Telemedicine has become indispensable in contemporary healthcare, reshaping patient care worldwide. The utilization of it has significantly risen in the Philippines, particularly during the pandemic, mirroring a global trend. Nevertheless, there is a dearth of studies regarding its pragmatic implementation among Filipino physicians, a crucial aspect for enhancing healthcare delivery. A qualitative analysis utilized in-depth interviews with experienced physicians in the Philippines. The researchers employed an inductive methodology to investigate how 13 physicians integrate telemedicine into their private medical practices. The selection of participants was purposeful, specifically targeting physicians with more than two years of experience in telemedicine. The qualitative data collected was subjected to a rigorous thematic analysis, comprehensively examining the current telemedicine integration situations. The examination of the data indicated a central theme: ‘Transcending Telemedicine’, emphasizing its influence that goes beyond being a mere technological tool. It overcomes time, space, and geography constraints, enhancing physicians’ ability to serve patients. There are four subcategories connected that contribute to or hinder the achievement of this goal: factors influencing adoption and factors influencing implementation and responses and reactions to telemedicine adoption. This paper contributes to the general understanding of telemedicine’s function in healthcare, specifically in the setting of a developing country. It emphasizes the necessity for continuous support and adjustment to maximize its benefits.